Government intervention in marriages of convenience between TV broadcasters and distributors - Donders, Karen (Javnost (Ljubljana), 2014)
Albeit largely neglected in communication sciences research, industrial convergence has put the relation between legacy content media like TV broadcasters and distributors (cable, satellite) firmly on the policy agenda. There seems to be an increasing awareness of the gatekeeping characteristics of mainstream as well as online video distribution, and the power distributors can exert vis-a-vis television broadcasters in terms of the bundling of services and pricing. The relation between TV broadcasters and distributors is increasingly characterised by conflicts. Because of public disputes between broadcasters and distributors, and threats of blackout, several governments across Europe are indeed discussing the necessity of regulatory intervention in order to decrease tension and promote cooperation in their media sectors. The article therefore questions how broadcasters have problematised their relation with distributors and put it on the policy agenda, whether it is up to governments to intervene in the relationship between broadcasters and distributors, and whether the proposed policy actions are likely to remedy the tensions in the marketplace.
Keywords: mass media; množični mediji; television; televizija; kabelska televizija; distribucija; financiranje; cene